Revisiting How and When Perceived Organizational Support Enhances Taking Charge: An Inverted U-Shaped Perspective. (November 2015) - Burnett, Meredith F.; Chiaburu, Dan S.; Shapiro, Debra L.; Li, Ning
Current theory and research suggest a positive linear relationship between perceived organizational support (POS) and employees' taking charge, or change-suggesting, behaviors. Via a sample of 89 subordinate-supervisor dyads, we hypothesize and test an inverted U-shaped relationship between employees' POS and their taking charge behaviors and the likelihood that this curvilinear pattern is accentuated when employees anticipate costs related to their taking charge. Results support both of these patterns. We conclude by discussing our findings' implications regarding future needed sensitivity on the part of managers as well as management scholars regarding how to gauge optimal levels of POS.